2009
DOI: 10.5194/acpd-9-5231-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A product study of the isoprene+NO<sub>3</sub> reaction

Abstract: Abstract. Oxidation of isoprene through reaction with NO3 is a significant sink for isoprene that persists after dark. The products of the reaction are multifunctional nitrates. These nitrates constitute a significant NOx sink in the nocturnal boundary layer and they likely play an important role in formation of secondary organic aerosol. Products of the isoprene+NO3 reaction will, in many locations, be abundant enough to affect nighttime radical chemistry and to persist into daytime where they may represent a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Table 2 summarizes the results of studies in the literature that report quantifying the yield of total alkyl nitrates from the isoprene + NO 3 reaction. Our observation of alkyl nitrate formation (70±8%) is equivalent to previously reported yields (65%-80%), within the combined experimental errors (Skov et al, 1992;Perring et al, 2009). The fact that multiple experiments conducted under different conditions (concentrations of isoprene and oxidants differing by more than a factor of 100) have all produced high yields of alkyl nitrates implies that the yield is robust and relatively insensitive to the peroxy radical chemistry, and supports findings that the isoprene + NO 3 reaction is possibly the single strongest source of alkyl nitrates in the atmosphere (Horowitz et al, 2007).…”
Section: Optimized Model Parameterssupporting
confidence: 90%
See 2 more Smart Citations
“…Table 2 summarizes the results of studies in the literature that report quantifying the yield of total alkyl nitrates from the isoprene + NO 3 reaction. Our observation of alkyl nitrate formation (70±8%) is equivalent to previously reported yields (65%-80%), within the combined experimental errors (Skov et al, 1992;Perring et al, 2009). The fact that multiple experiments conducted under different conditions (concentrations of isoprene and oxidants differing by more than a factor of 100) have all produced high yields of alkyl nitrates implies that the yield is robust and relatively insensitive to the peroxy radical chemistry, and supports findings that the isoprene + NO 3 reaction is possibly the single strongest source of alkyl nitrates in the atmosphere (Horowitz et al, 2007).…”
Section: Optimized Model Parameterssupporting
confidence: 90%
“…Kwok et al (1996) yields of 3.5% for both MVK and MACR. Perring et al (2009) observed a 7% yield of the sum of MVK and MACR using PTR-MS. Skov et al (1992) and Perring et al (2009) measured product yields by adding isoprene to a chamber that was initially charged with ppm levels of N 2 O 5 . Kwok et al (1996) added isoprene first as we did, but then injected N 2 O 5 in ppm steps.…”
Section: Optimized Model Parametersmentioning
confidence: 95%
See 1 more Smart Citation
“…Specific individual gas phase RONO 2 molecules have been observed using gas chromatography (e.g. (2)(3)(4)(5)(6)) and chemical ionization mass spectrometry (7)(8)(9), and the total of gas and aerosol RONO 2 (total Alkyl Nitrates, ΣAN) has been observed by Thermal Dissociation Laser Induced Fluorescence (TD-LIF) (1,(10)(11)(12). Recently there has been growing interest in understanding the partitioning of RONO 2 to atmospheric particles (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Difunctional organic nitrate compounds can form when NO3 reacts with unsaturated hydrocarbons in air, and the chemistry of these processes was discussed by Barnes et al 10 Reaction of NO3 with isoprene is an important example, 11 producing products such as nitrooxy carbonyls and, in principle, organic dinitrate species. For example, in a chamber study, Rollins et al 12 observed dinitrate species produced in the reaction of primary isoprene nitrates with NO3.…”
Section: Introductionmentioning
confidence: 99%